Hiring Library Technicians in Academic Libraries: Revising, Rejecting, and Reclaiming the Process - Neigel, Christina; Manhas, Ashley; Buhler, Shawna; Greenly, Glen; Samborski, Dalene (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2024)
Using métissage as a method of inquiry, this paper is the outcome of reflections of a Canadian academic library hiring committee that consists of both librarians and library technicians that disrupted local hiring practices in the effort to create a more human-centred, inclusive, and thoughtful process when hiring for two library technician vacancies. Through the writing and mixing of texts, three themes emerged that capture the shared experiences of the committee and serve as an example of how reflective practice can take shape among different types of employees in a busy academic library. This process helped to empower members of the hiring committee to question and contribute to the hiring process in new ways. Despite the limits of time, this project reveals that efforts can be made to create a space for a hiring committee, comprised of library employees with different levels of workplace power, to critique and modify practices to improve approaches to hiring. These improvements go beyond creating a welcoming environment for candidates and include changes to the way current employees feel about their contributions and their engagement in the work.